2008
DOI: 10.1140/epjst/e2008-00729-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to parameters of STIRAP in a Cooper Pair Box

Abstract: The rapid experimental progress in the field of superconducting nanocircuits gives rise to an increasing quest for advanced quantum-control techniques for these macroscopically coherent systems. Here we demonstrate theoretically that stimulated Raman adiabatic passage (STIRAP), a well-established method in quantum optics, should be possible with the quantronium setup of a Cooperpair box. We find the parameters which optimize the procedure and show how the scheme appears to be robust against decoherence and sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We have shown in previous works that this has no effect for CPB's in the charge-phase regime, due to the large anharmonicity of the spectrum, even in the presence of markovian noise 8,9,26 . Therefore we will safely study the effect of noise in the lowest three-level subspace.…”
Section: A Implementation Of the λ Systemmentioning
confidence: 89%
“…We have shown in previous works that this has no effect for CPB's in the charge-phase regime, due to the large anharmonicity of the spectrum, even in the presence of markovian noise 8,9,26 . Therefore we will safely study the effect of noise in the lowest three-level subspace.…”
Section: A Implementation Of the λ Systemmentioning
confidence: 89%
“…Among the other recent papers that have discussed the detrimental effect of stochastic processes on STIRAP we note Refs. [62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Fluctuationsmentioning
confidence: 99%
“…In this case the terms neglected are rapidly oscillating in the rotating frame, and only produce a small and fast modulation in the dynamics. The approximation is supported by simulations of the full Hamiltonian (4), using more than ten energy levels 15,28 for the usual operating region near q g ¼ 1=2. It is worth stressing the dependence of the e®ective HamiltonianH ðq g Þ on the bias charge q g .…”
Section: 26mentioning
confidence: 95%
“…15 it has been shown that secular dephasing between the above two states does not produce relevant e®ects during population transfer. A careful analysis 28 has allowed us to optimize parameters for STIRAP in the presence of high-frequency noise, showing that operating at q g ¼ 0:47 already provides su±-cient coupling q 02 .…”
Section: E®ects Of Low-frequency Noise In the Quantroniummentioning
confidence: 99%